Educators’ intention to use tangible and graphical experimentation with Arduino and Micro:bit - Sokratis Tselegkaridis; Theodosios Sapounidis; Serafeim A. Triantafyllou (Discover Education)
Abstract Nowadays, the educational process is enriched with technological tools such as Arduino and Micro:bit. These tools offer both tangible and graphical interaction, however, widespread adoption by educators faces limitations. Many educators hesitate to utilize them, primarily due to lacking training. Therefore, this study examines educators’ behavioral intentions to use Arduino and Micro:bit to enhance teaching and learning. Sixty-one primary and secondary school educators participated without prior knowledge of electronic circuits or programming. The examination aimed to assess: (a) educators’ preferences between tangible and virtual experimentation, and (b) factors influencing educators’ behavioral intention to use Arduino and Micro:bit. The statistical analysis encompassed a range of methods, including factor analysis, and linear regression. The findings indicated a preference among educators for implementing Arduino circuits through simulation, while no preference differences were observed between simulation and a real board for the Micro:bit. Additionally, linear regressions revealed that Arduino and Micro:bit follow different paths leading to the behavioral intention to use. Specifically, with Arduino, the intention to use is primarily influenced by users’ perceived usefulness. Conversely, in the case of Micro:bit, the intention to use is mainly driven by users’ attitudes towards its use. Hence, enhancing educators’ perceived usefulness and ease of use of Arduino Uno and Micro:bit is essential for fostering their intention to integrate these tools into their teaching practices.